Adoption and impacts of improved post-harvest technologies on food security and welfare of maize-farming households in Tanzania: a comparative assessment - Mutungi, C.; Manda, J.; Feleke, S.; Abass, A.; Bekunda, Mateete A.; Hoeschle-Zeledon, I.; Fischer, G. (Springer, 2023)
During the last decade, post-harvest losses (PHL) reduction has been topping the agenda of governments as a pathway for addressing food security, poverty, and nutrition challenges in Africa. Using survey data from 579 households, we investigated the factors that affect farmers’ decisions to adopt post-harvest technologies: mechanized shelling, drying tarpaulins, and airtight storage validated for reducing PHL in Tanzania’s maize-based systems, and the impacts on households’ food security and welfare. Mechanized shelling addressed a labor issue, while tarpaulins and airtight storage addressed product quality and quantity concerns. The results revealed large farm sizes and location in higher production potential zones (proxies for higher production scale) and neighbors' use of the technologies as universal drivers for adoption. Access to credit and off-farm income were unique determinants for airtight storage, while group membership increased the probability of adopting drying tarpaulin and airtight storage. The technologies have positive impacts on food security and welfare: drying tarpaulins and airtight storage significantly increased food availability (18–27%), food access (24–26%), and household incomes (112–155%), whereas mechanized shelling improved food and total expenditures by 49% and 68%, respectively. The share of total household expenditure on food decreased by 42%, 11%, and 51% among tarpaulin, mechanized shelling, and airtight storage adopter households, signaling significant improvements in food security and reductions in vulnerability. The results point to the need for policy support to enhance the adoption of these technologies, knowledge sharing among farmers, and financial resources access to support investments in the technologies.